Sistem Pendukung Keputusan Seleksi Bantuan Operasional Madrasah Menggunakan Metode Weighted Aggregatedsum Product Assessment Berbasis Android Pada Kementerian Agama Kabupaten Pohuwato - Muh salim (JSAI (Journal Scientific and Applied Informatics), 2020)
The Government has a responsibility to educate every one of its people and has become its duty to develop every potential of its people, especially among school ages, to become human beings who believe and fear the Almighty God, Noble, healthy, knowledgeable, capable, creative, independent. In the field of religious education, in this case, the Islamic religion through Islamic educational institutions conducted in Madrasah has made a great contribution to the development of the nation. Through the madrasah, it is able to give birth to generations of Islamic characters and national knowledge. With the advancement of technology, every decision can be taken quickly and accurately through a decision support system. The problem found in research was the selection of the Madrasah operational assistance, with a budget that has limited funds, election or screening is done as possible by checking one by one file and requiring time Older, file buildup allows some missing files to be misplaced. The method used is a descriptive method and the results of the study concluded that with the decision support system helped the Ministry of Religion Pohuwato to distribute operational assistance in the madrasas evenly.